Study of sunflower crop care technology - Nasiyev, B. N.; Yesenguzhina, A .N. (intellect, idea, innovation- 2020. (Костанай)., 2020)
Nowadays, a complex of intensive soil treatments is used to eliminate weeds on sunflower crops, including pre-sowing cultivation at medium, early sowing periods, pre-emergence and emergence harrowing, 3 ... 4 interrow cultivations using weeding harrows and dusting devices. It leads to soil dispersion, which is extremely harmful in general, and in areas subject to erosion, in particular. In addition, root system and above-ground organs of sunflower receive numerous injuries in post-exposure harrowing and inter-row treatments, which does not contribute to normal vital activity of a plant organism. In this regard, a chemical method of killing weed plants is of great interest. Using effective herbicides reduces negative effect of weeds from the earliest period of sunflower vegetation, and it is possible to reduce the number of mechanical treatments of soil. As a result of the carried out studies, data were obtained, allowing to estimate productivity of sunflower crops in conditions of 1 dry-steppe zone of West Kazakhstan region depending on pre-sowing treatments. According to the data of studies in the zone of dry steppes of West Kazakhstan, in the cultivation of sunflower along with harrowing and one pre-plant cultivation, it is advisable to use Roundup herbicide in a dose of 2 l/ha.
Keywords: рк; масличные культуры; sunflower; weeds; herbicides; pre-sowing treatment; yield; oil; подсолнечник; сорные растения; гирбициды; предпосевная обработка; отечественное издание; научный журнал; периодическое издание; журнал коксон